2022
DOI: 10.1002/ece3.8937
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic niche overlap between sympatric Australian snubfin and humpback dolphins

Abstract: Ecological niche theory predicts the coexistence of closely related species is promoted by resource partitioning in space and time. Australian snubfin ( Orcaella heinsohni ) and humpback ( Sousa sahulensis ) dolphins live in sympatry throughout most of their range in northern Australian waters. We compared stable isotope ratios of carbon (δ 13 C) and nitrogen (δ 15 N) in their skin to investigate resource partitioning b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 103 publications
0
4
0
Order By: Relevance
“…The overlapping of food resources between S. yunnanensis and S. nagaensis is consistent with the adoption of strategies for food resources observed in other sympatric species. For example, a feather isotope analysis of three sympatric species of closely related seabirds revealed substantial overlap in food resources [21], and Australian snubfin and humpback dolphins that co-exist in the same domain have overlapping dietary resources but different dietary preferences [37].…”
Section: Discussionmentioning
confidence: 99%
“…The overlapping of food resources between S. yunnanensis and S. nagaensis is consistent with the adoption of strategies for food resources observed in other sympatric species. For example, a feather isotope analysis of three sympatric species of closely related seabirds revealed substantial overlap in food resources [21], and Australian snubfin and humpback dolphins that co-exist in the same domain have overlapping dietary resources but different dietary preferences [37].…”
Section: Discussionmentioning
confidence: 99%
“…This concurs with previous studies of niche partitioning between these species 44 , 46 . Elsewhere, it has been shown that, although habitat partitioning may occur, niche partitioning is mediated by differences in trophic niches 35 , 36 , 73 . Around the North West Cape, the trophic interactions of humpback and bottlenose dolphins are poorly understood, however, opportunistic observations of both species foraging suggest that the species may target different prey.…”
Section: Discussionmentioning
confidence: 99%
“…As it is possible for different food resources to show similar isotopic composition [ 76 , 77 ], we cannot completely exclude the possibility of trophic segregation based on stable isotope data alone. Two coastal delphinid species in Queensland, Australia, the Australian humpback ( Sousa sahulensis ) and the snubfin dolphin ( Orcaella heinsohni ), also showed high isotopic niche overlap [ 78 ]. In this case, their co-existence was attributed to subtle differences in habitat use and prey selection [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two coastal delphinid species in Queensland, Australia, the Australian humpback ( Sousa sahulensis ) and the snubfin dolphin ( Orcaella heinsohni ), also showed high isotopic niche overlap [ 78 ]. In this case, their co-existence was attributed to subtle differences in habitat use and prey selection [ 78 ]. However, those two species are similar in size and can exploit the same prey species.…”
Section: Discussionmentioning
confidence: 99%